Saturday at the food pantry - O'Neill, Diane, 1955- (Albert Whitman & Company, 2021)
Molly and her mom do not always have enough food, so when they visit their local food pantry Molly she sees her classmate Caitlin who is embarrassed to be there, so Molly helps Caitlin realize everyone needs help sometimes.